Advanced (bio)fouling resistant surface modification of PTFE hollow-fiber membranes for water treatment - Taghavian, Hadi; Černík, Miroslav; Dvořák, Lukáš (Scientific reports, 2023)
Membrane surface treatment to modify anti-(bio)fouling resistivity plays a key role in membrane technology. This paper reports on the successful use of air-stimulated surface polymerization of dopamine hydrochloride incorporated ZnO nanoparticles (ZnO NPs) for impeding the intrinsic hydrophobicity and low anti-(bio)fouling resistivity of polytetrafluoroethylene (PTFE) hollow-fiber membranes (HFMs). The study involved the use of pristine and polydopamine (Pdopa) coated PTFE HFMs, both with and without the presence of an air supply and added ZnO NPs. Zeta potential measurements were performed to evaluate the dispersion stability of ZnO NPs prior to immobilization, while morphological characterization and time-dependency of the Pdopa growth layer were illustrated through scanning electron microscopy. Pdopa surface polymerization and ZnO NPs immobilization were confirmed using FT-IR and EDX spectroscopy. Transformation of the PTFE HFM surface features to superhydrophilic was demonstrated through water contact angle analysis and the stability of immobilized ZnO NPs assessed by ICP analysis. Anti-fouling criteria and (bio)fouling resistivity performance of the surface-modified membranes were assessed through flux recovery determination of bovine serum albumin in dead-end filtration as well as dynamic-contact-condition microbial evaluation against Staphylococcus spp. and Escherichia coli, respectively. The filtration recovery ratio and antimicrobial results suggested promising surface modification impacts on the anti-fouling properties of PTFE HFM. As such, the method represents the first successful use of air-stimulated Pdopa coating incorporating ZnO NPs to induce superhydrophilic PTFE HFM surface modification. Such a method can be extended to the other membranes associated with water treatment processes.
Keywords: oxid zinečnatý; polytetrafluoroethylen; Dopamine; Spectroscopy, Fourier Transform Infrared; Zinc Oxide; Escherichia coli; Polytetrafluoroethylene; dopamin; spektroskopie infračervená s Fourierovou transformací